Langkah-Langkah dalam Mewujudkan Keluarga Sakinah - Hidayani Syam; Elvi Nasari; Jeri Noviandi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
In Islam, the concept of a sakinah family—a household built on love (mawaddah), affection (rahmah), and based on faith and devotion to Allah SWT—is ideal. Al-Qur'an Surah Ar-Rum verse 21 explicitly states that the purpose of marriage is to achieve peace (sakinah). However, creating a sakinah family in the midst of modernization is not an easy matter. Modern developments bring challenges such as economic pressure, modern lifestyle, lack of healthy communication, and the influence of social media, which can threaten harmony. Therefore, strategic and planned steps are needed to form a family that is harmonious, stable and has an Islamic nuance.